Comparative Morphological Analysis of Precancerous Lesions and Conditions by Clinical Examination, Chemiluminescence, and Toluidine Blue - MunBhawni Bagga; Anand C Kumar; Dipti Bhatnagar (Wolters Kluwer Medknow Publications, 2017)
Introduction: Oral squamous cell carcinoma accounts for up to 50% of malignant tumors in Asian countries and is very common in India, Pakistan, and Taiwan. Currently, the most effective way of combating oral cancer is by early diagnosis followed by adequate treatment. As visualization is the principal strategy used to assess the patient's lesions at risk of malignant transformation, any procedure which highlights such lesions aids the clinician. Aim: The present study was carried out to compare the usefulness and validity of clinical examination, chemiluminescence, and toluidine blue in assessing the precancer. Materials and Methods: The study sample consisted of 100 subjects, 50 each of oral leukoplakia and oral submucous fibrosis. Evaluation of suspicious lesion was carried out by clinical examination, chemiluminescence, toluidine blue with the gold standard of histopathological diagnosis. The chemiluminescent and toluidine blue examination were evaluated by two observers who are unaware of the clinical examination. Results: Chemiluminescence was found to be better than toluidine blue and clinical examination by both the observers (P < 0.05). Chemiluminescence was found to be better in visualization of leukoplakic lesions by both the observers (kappa >0.900). The visualization, exact extent, borders, and surface texture of lesions were revealed accurate by chemiluminescence followed by toluidine blue and clinical evaluation (P < 0.05). The sensitivity and specificity was more reliable for chemiluminescence (75 and 54.7%) than the toluidine blue (57.4 and 44.1%). Our observations suggest that the mild and severe dysplasia of the lesions were well appreciated by chemiluminescence. Conclusion: Chemiluminescence and toluidine blue cannot be compared with histopathology as these are adjunctive aids in early diagnosis of oral precancer and cancer. Hence their adjunctive value is of great importance to be used as a chair-side investigation and for mass screening of oral cancer.